Consolidation and permeability characteristics at DSDP Sites 87-582, 87-583, and 87-584 - Mark W Johns (PANGAEA, 1986)
The results of nine consolidation and permeability tests are presented for sediment samples from the Japan Trench and Nankai Trough sites of Leg 87. Coring and degassing disturbance results in an underconsolidated state for most Site 582 samples; however, the compressional effects of the subduction zone and high sediment accumulation rates may also play a role in causing underconsolidation. Samples collected at Site 583 exhibit similar evidence of disturbance but are slightly overconsolidated, confirming the possibility of sediment erosion at this site. The highly diatomaceous sediments at Site 584 are all overconsolidated, but the trend of overconsolidation decreases with depth. Disturbances of the diatom clay structure may increase the sediment compressibility and create this apparent overconsolidation
Supplement to: Johns, MW (1986): Consolidation and permeability characteristics of Japan Trench and Nankai Trough sediments from Deep Sea Drilling Project Leg 87, Sites 582, 583, and 584. In: Kagami, H; Karig, DE; Coulbourn, WT; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 87, 843-849, https://doi.org/10.2973/dsdp.proc.87.129.1986